Antioxidant and antiglycemic potential of Peltophorum pterocarpum plant parts - Manaharan, T.; Teng, L.L.; Appleton, D.; Ming, C.H.; Masilamani, T.; Palanisamy, U.D. (Elsevier, 2011)
The leaf and bark extracts of Peltophorum pterocarpum were evaluated for their DPPH, ARTS, and galvinoxyl radicals scavenging activity, phenolic content, alpha-glucosidase, alpha-amylase and aldose reductase inhibition, and advanced glycation end-products formation inhibition activities. These extracts showed a far more significant antiglycemic activity compared to the commercial carbohydrate inhibitor, acarbose. The active compound in P. pterocarpum leaf extracts was identified to be quercetin-3-O-beta-D-galactopyranoside. Our findings provide a strong rationale for further in vivo studies and to establish P. pterocarpum's capability as an antiglycemic agent. (C) 2011 Elsevier Ltd. All rights reserved.